2015
DOI: 10.1093/petrology/egv020
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Thermodynamic Model for Melting of Peridotite in the System NCFMASOCr

Abstract: A new thermodynamic model is presented for calculating phase relations in peridotite, from 0Á001 to 60 kbar and from 800 C to liquidus temperatures, in the system NCFMASOCr. This model system is large enough to simulate phase relations and melting of natural peridotite and basaltic liquids. Calculations in the program THERMOCALC illustrate mantle phase relationships and melting conditions, specifically for the peridotite composition KLB-1. The garnet-spinel transition zone intersects the solidus at 21Á4-21Á7 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
229
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(236 citation statements)
references
References 90 publications
(182 reference statements)
5
229
2
Order By: Relevance
“…However, Green et al (2012) and Jennings and Holland (2015) argue that the pressure of the garnet-spinel transition was overestimated in previous experimental studies, largely due to the simplicity of the phase systems used (i.e., Mg-Al-Si rather than Ca-Mg-Al-Si). Jennings and Holland (2015) demonstrate that their model compares well to existing studies, provided that simplifying corrections are applied, notably allowing for Ca activity within garnet. Samples from RGR include 671, 672, 674-676, 678, 695, 699, 860, 864-866, 869, 870, 875, 879, 882, 883, 888, 894, 895, 898, 6100, 6102-6104, 6108, 6110, 6130, 6140, 6143, 6151, 6152, 6155, 6157, 6158, 6185, 6187, 8101, 8103, 8107, 8109-8112, 8128, 8129, 8134, 8136, 8138-8140, 8144, 8157, 8159-8161, and 8164 from R. Thompson et al (2005).…”
Section: Melting Model and Its Applicationmentioning
confidence: 98%
See 1 more Smart Citation
“…However, Green et al (2012) and Jennings and Holland (2015) argue that the pressure of the garnet-spinel transition was overestimated in previous experimental studies, largely due to the simplicity of the phase systems used (i.e., Mg-Al-Si rather than Ca-Mg-Al-Si). Jennings and Holland (2015) demonstrate that their model compares well to existing studies, provided that simplifying corrections are applied, notably allowing for Ca activity within garnet. Samples from RGR include 671, 672, 674-676, 678, 695, 699, 860, 864-866, 869, 870, 875, 879, 882, 883, 888, 894, 895, 898, 6100, 6102-6104, 6108, 6110, 6130, 6140, 6143, 6151, 6152, 6155, 6157, 6158, 6185, 6187, 8101, 8103, 8107, 8109-8112, 8128, 8129, 8134, 8136, 8138-8140, 8144, 8157, 8159-8161, and 8164 from R. Thompson et al (2005).…”
Section: Melting Model and Its Applicationmentioning
confidence: 98%
“…2, 11, 13b, 18, 19b, 22, 23b, 26, 27, 30, 31b, 32-35, SC 07 03, and SC 07 05 generously provided by T. Plank (personal communication, 26 September 2015) and Plank and Forsyth (2016). By contrast, increasing concentrations of Cr and Fe 3+ within peridotite tend both to increase the thickness of the transition and to cause a shift to greater pressures due to the greater stability of spinel (Jennings & Holland, 2015;Klemme & O'Neill, 2000). Jennings and Holland (2015) demonstrate that their model compares well to existing studies, provided that simplifying corrections are applied, notably allowing for Ca activity within garnet.…”
Section: Melting Model and Its Applicationmentioning
confidence: 99%
“…Among the available sets of endmember properties and solution models for Cr-bearing phases (e.g. Klemme et al 2009;Ziberna et al 2013, Jennings andHolland 2015), we adopted the model suggested by Klemme et al (2009) which was later on refined by Ziberna et al (2013). This model shows good agreement with the available experimental data in both Cr-poor and Cr-rich mantle Compositions from LS1 to BN4 were taken from Stern et al (1999) and were normalized to 100 wt% after removing TiO compositions (e.g.…”
Section: Methodsmentioning
confidence: 97%
“…However, the recent advances in thermodynamic modelling techniques and refinements of thermodynamic databases may help to investigate subsolidus phase relations in simple (e.g. Klemme 2004;Green et al 2012) and complex (Asimow and Ghiorso 1998;Klemme et al 2009, Ziberna et al 2013, Jennings and Holland 2015 mantle compositions. In two previous papers, Klemme et al (2009) and Ziberna et al (2013) focused more on methods and calibration of a thermodynamic model for Cr-bearing mantle rocks, so the aim of this paper is to show how this thermodynamic model may be applied to investigate processes in the upper mantle.…”
mentioning
confidence: 99%
“…The chemical thermodynamic approach developed over several years by Ghiorso (Ghiorso, 1985;Ghiorso and Sacks, 1995;Ghiorso et al, 2002) specifically includes the melt phase and provides a more rigorous understanding of the petrological evolution at different P,T,X,fO 2 conditions. Recently new thermodynamic descriptions of mantle melting have been presented (Ueki and Iwamori, 2014;Jennings and Holland, 2015). An advantage of the thermodynamic formulation is that, within certain limits, it creates a framework that allows also to make predictions at conditions not interested by experimental studies.…”
Section: Introductionmentioning
confidence: 99%